Short-chain fatty acids, secondary bile acids and indoles: gut microbial metabolites with effects on enteroendocrine cell function and their potential as therapies for metabolic disease - Masse, Karly E.; Lu, Van B. (Frontiers in Endocrinology, 2023)
The gastrointestinal tract hosts the largest ecosystem of microorganisms in the body. The metabolism of ingested nutrients by gut bacteria produces novel chemical mediators that can influence chemosensory cells lining the gastrointestinal tract. Specifically, hormone-releasing enteroendocrine cells which express a host of receptors activated by these bacterial metabolites. This review will focus on the activation mechanisms of glucagon-like peptide-1 releasing enteroendocrine cells by the three main bacterial metabolites produced in the gut: short-chain fatty acids, secondary bile acids and indoles. Given the importance of enteroendocrine cells in regulating glucose homeostasis and food intake, we will also discuss therapies based on these bacterial metabolites used in the treatment of metabolic diseases such as diabetes and obesity. Elucidating the mechanisms gut bacteria can influence cellular function in the host will advance our understanding of this fundamental symbiotic relationship and unlock the potential of harnessing these pathways to improve human health.